Improved survival using intensity‐modulated radiation therapy in head and neck cancers: A SEER‐Medicare analysis. Issue 5 (13th January 2014) - Beadle, Beth M.; Liao, Kai‐Ping; Elting, Linda S.; Buchholz, Thomas A.; Ang, K. Kian; Garden, Adam S.; Guadagnolo, B. Ashleigh
Abstract : BACKGROUND: Intensity‐modulated radiation therapy (IMRT) is a technologically advanced, and more expensive, method of delivering radiation therapy with a goal of minimizing toxicity. It has been widely adopted for head and neck cancers; however, its comparative impact on cancer control and survival remains unknown. The goal of this analysis was to compare the cause‐specific survival (CSS) for patients with head and neck cancers treated with IMRT versus non‐IMRT from 1999 to 2007. METHODS: CSS was determined using the Surveillance, Epidemiology, and End Results (SEER)‐Medicare database and analyzed regarding treatment details, including the use of IMRT versus non‐IMRT, using claims data. Hazard ratios (HRs) were estimated by the frailty model with a propensity score matching cohort and instrumental variable analysis. RESULTS: A total of 3172 patients were identified. With a median follow‐up of 40 months, patients treated with IMRT had a statistically significant improvement in CSS compared with those treated with non‐IMRT (84.1% versus 66.0%; P < .001). When each anatomic subsite was analyzed separately, all respective subgroups of patients treated with IMRT had better CSS than those treated with non‐IMRT. In multivariable survival analyses, patients treated with IMRT were associated with better CSS (HR = 0.72, 95% confidence interval = 0.59 to 0.90 for propensity score matching; HR = 0.60, 95% confidence interval = 0.41 to 0.88 for instrumental variable analysis). CONCLUSIONS: Patients with head and neck cancers who were treated with IMRT experienced significant improvements in CSS compared with patients treated with non‐IMRT techniques. This suggests there may be benefits to IMRT in cancer outcomes, in addition to toxicity reduction, for this patient population. Cancer 2014;120:702–710 . © 2013 American Cancer Society . Abstract : The goal of this analysis was to compare the cause‐specific survival for patients with head and neck cancers treated with intensity‐modulated radiation therapy (IMRT) versus non‐IMRT using the Surveillance, Epidemiology, and End Results linked with Medicare (SEER‐Medicare) database. Patients with head and neck cancers treated with IMRT experienced significant improvements in cause‐specific survival compared with patients treated with non‐IMRT techniques.